Dividend Policy of Russian Companies: Impact of Board of Directors - MirzoyanAshot; SchukinaPolina; GalichAnastasiia (Journal of Corporate Finance Research / Корпоративные Финансы | ISSN: 2073-0438, 2025)
The purpose of this study is to examine the relationship between corporate governance and dividend policy of Russian companies based on two theoretical models: the outcome model and the substitution model, which imply the opposite nature of the relationship between corporate governance and dividend payments. The main characteristics of the board of directors as a key mechanism of corporate governance are considered: women representation on the board, independence of the board, the share of directors with foreign experience, frequency of meetings, permanence of the board composition, the average tenure of board members, concurrent independent directors and CEO duality. The novelty of the study lies in analyzing a wide range of characteristics of the boards of directors of Russian public companies whose shares are traded on the Moscow Exchange. Using a sample of 31 Russian companies for the period from 2010 to 2022, fixed-effects regression models showed that the women representation on the board of directors, concurrent independent directors and permanence of the board composition are positively related to dividend payments of Russian companies. No significant relationship was found between dividend payments and such corporate governance characteristics as board independence, the share of directors with foreign experience, frequency of board meetings, and the CEO’s membership in the board of directors. This may indicate the specifics of governance in Russian companies, where a high concentration of majority shareholders and government involvement may limit the influence of independent management bodies. The results of the study may be useful for company managers, investors and regulators to optimize corporate governance and make decisions regarding dividend policy.